Resistance training preserves high-intensity interval training induced improvements in skeletal muscle capillarization of healthy old men: a randomized controlled trial - Aurel B. Leuchtmann (Nature Portfolio, 2020)
Abstract Skeletal muscle capillarization is a determining factor in gas and metabolite exchange, while its impairments may contribute to the development of sarcopenia. Studies on the potential of resistance training (RT) to induce angiogenesis in older muscles have been inconclusive, and effects of sequential endurance training (ET) and RT on capillarization are unknown. Healthy older men (66.5 ± 3.8 years) were engaged in either 12 weeks of habitual course observation (HC) followed by 12 weeks of RT (n = 8), or 12 weeks of high-intensity interval training (HIIT) followed by 12 weeks of RT (n = 9). At baseline, following 12 and 24 weeks, m. vastus lateralis biopsies were obtained. (Immuno-)histochemistry was used to assess indices of muscle fiber capillarization, muscle fiber morphology and succinate dehydrogenase (SDH) activity. Single periods of RT and HIIT resulted in similar improvements in capillarization and SDH activity. During RT following HIIT, improved capillarization and SDH activity, as well as muscle fiber morphology remained unchanged. The applied RT and HIIT protocols were thus similarly effective in enhancing capillarization and oxidative enzyme activity and RT effectively preserved HIIT-induced adaptations of these parameters. Hence, both, RT and HIIT, are valid training modalities for older men to improve skeletal muscle vascularization.